A revision of the genus Fabricia Blainville, 1828 (Polychaeta: Sabellidae: Fabriciinae) - Fitzhugh, K. (Sarsia, 1990)
The Fabriciinae genus Fabricia Blainville is revised. In the past, the type species designation for the genus has been confused; explicit designations have included Tubularia fabricia Mueller and Amphicora sabella Ehrenberg. The type species is actually T. stellaris Mueller, by monotypy. A neotype is designated and described for F. stellaris stellaris from the type locality.
Kristian Fauchald's Polychaeta DB